The popular in education: between myth and imaginary - Jiménez García, Marco Antonio; Valle Vázquez, Ana María (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This article purposes to analyze the popular education subject, between myth and imaginary, due to the prevailing need to reconceptualize and revitalize the autonomy of the social demands in a world where virtually no collective and alternative attempt to organize, confront and transform the globalized capitalism comes true, all liberating or emancipatory attempt fades away or is integrated to the dominant discourse. The thesis here argues that myth and imaginary are popular education elements, and that rejection of the popular is the negation of all political and cultural action. For us, myth is the word that flows and makes sense to the whole community, it is the reason that does not deny the no reason constitutive of culture. In the same way the imaginary is formed by social imaginary meanings that do not exclude the insignificance and that emanate from the incessant and the undetermined creation. Thus, popular education between myth and imagination accounts, in theory and in practice, for the sense and nonsense of any society and culture.